Challenges of Urban Living Labs towards the Future of Local Innovation - Ersoy, Aksel (2020)
Finding new approaches to overcome complex urban problems such as climate change has always been of interest to policymakers and academics. The changing dynamics of urban development result in the diversification of new practices during which experimentation is used to inform urban practice. Amongst these approaches, urban living labs (ULLs) have become a popular form of urban experimental innovation in many countries in the last decade. These ULLs respond to the increased complexity of future challenges calling for local solutions that acknowledge the local conditions—political, technical, and social. Even though a great deal of attention has been given to this form of urban innovation, there has been little consideration of the learning and innovation processes within ULLs. Based on a comparative case study of three innovation projects in a ULL in the city of Amsterdam, we analyse and discuss the claims of ULLs regarding innovation and the different orders of learning they foster. We argue that in the processes of experimentation within ULLs, combining mechanisms of learning and innovation is key to promoting the development of particular local solutions. However, since the learning processes are especially concerned within a particular ULL learning setting, there is a mismatch between the expectations of policymakers, industry, citizens, and knowledge institutes, as well as how the lessons learned can be useful for other contexts.